2014
DOI: 10.1021/am504190a
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection of Circulating OncomiRs from Body Fluids for Prostate Cancer Staging Using Nanographene Oxide

Abstract: Circulating oncomiRs are highly stable diagnostic, prognostic, and therapeutic tumor biomarkers, which can reflect the status of the disease and response to cancer therapy. miR-141 is an oncomiR, which is overexpressed in advanced prostate cancer patients, whereas its expression is at the normal levels in the early stages of the disease. On the other hand, miR-21 is significantly elevated in the early stage, but not in the advanced prostate cancer. Here, we have demonstrated simultaneous detection of exogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 33 publications
2
74
0
Order By: Relevance
“…To study how miRNAs regulate AR signaling, it is necessary to identify their targets. [15] reported that miR-141-3p expression is at normal levels in early PCa, which is in accordance with our findings. Using deep-sequencing analysis, we found that miR-141-3p expression was decreased by 1.26-fold in early PCa compared to that in BPH (P < 0.05), and confirmed a similar 1.17-fold decrease in early PCa compared to that in BPH (P = 0.2053) by qRT-PCR.…”
Section: Discussionsupporting
confidence: 93%
“…To study how miRNAs regulate AR signaling, it is necessary to identify their targets. [15] reported that miR-141-3p expression is at normal levels in early PCa, which is in accordance with our findings. Using deep-sequencing analysis, we found that miR-141-3p expression was decreased by 1.26-fold in early PCa compared to that in BPH (P < 0.05), and confirmed a similar 1.17-fold decrease in early PCa compared to that in BPH (P = 0.2053) by qRT-PCR.…”
Section: Discussionsupporting
confidence: 93%
“…This is expected to be a non- or minimally invasive approach to diagnose early-stage prostate cancer. 49 …”
Section: Diagnosis Of Systematic Diseases By Salivamentioning
confidence: 99%
“…This is currently needed because the blood level of the gold standard marker for prostate cancer, PSA, do not always correlate with disease stage and aggressiveness of the malignancy [57]. For example, miR-21 is significantly elevated in the early stage, but not in advanced prostate cancer [58] and miR-16 is up-regulated in plasma of metastatic prostate cancer patients, but down-regulated in primary or metastatic prostate cancer tissues [59]. Additionally, other miRNAs have been reported to be detected in blood exosomes in metastatic prostate cancer patients [60][61][62][63].…”
Section: Exosomes and Prostasomesmentioning
confidence: 99%